Strategic analysis of BNI in the Czech Republic - Mestdagh, Simon; Brunet-Thornton, Richard; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This strategic analysis aims to provide the national director and the members of the leadership team of BNI in the Czech Republic with summarized external trends, internal developments in comparison to competitors and recommendations based on the results of the analyses, accounting for the dynamic nature of the business environment and the unpredictable fluctuations in both global and local political and economic conditions. The findings have shown that the organization has had a good first year, nearly achieving the average number of active members for a chapter, the development of further chapters demonstrates the organization's goal of reaching 200 active members by the end of 2024. However, with external threats such as high energy costs and ongoing geopolitical conflicts, BNI CZ must ensure their members feel confident to keep networking and developing the organization. Their large competitive advantage due to their brand strength and global networking access does make them a powerful force though and positions them as leaders in the Czech networking industry.
Vedoucí práce: Richard Brunet-Thornton
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses